Nutritional status, body composition and health conditions of the Karen hill tribe children aged 1-6 years in Northern Thailand - Prasong Tienboon (2018)
Introduction: In Thailand, according to the national nutrition survey of the Thai population who live in the cities by the Ministry of Public Health, about 12% of preschool children aged 1-6 years were malnourished. The rate of malnutrition is much higher among mountain minority ('hill tribe') children than city children. This paper reports a study of malnutrition, body composition and health conditions of Karen hill tribe children aged 1-6 years in Thailand. Methods: All children aged 1-6 years (N = 158; 83 boys, 75 girls) from the three Karen villages (Mae Hae Tai, Mae Yot, Mae Raek) of Mae Chaem district in the north of Thailand were studied. Anthropometric measurements of all children were obtained and body composition data were derived. All children were examined by a qualified medical doctor. A stool sample and blood smear for malaria from all children were examined by a well qualified medical technologist. Results: All families of the study boys and girls had incomes lower than the Thailand poverty line (US $ 1,000/year). There were no significant differences in weight, height or body mass index of boys and girls from each of the three villages. Malnutrition in children were found 85.5% by using weight-for-age, 73% by height-for-age (stunting) and 48.4% by weight-for-height (wasting). Boys had more total body fat mass than girls. However, all of them had low lean body mass and fat mass. Nearly all children (98%) suffered from either upper respiratory tract infection, skin infection, scabies and/or diarrhoea. Also, nearly all of them (97%) had scaly and dry skin over their chest walls and legs. About 10% of children had either angular stomatitis (5%) or bleeding per gums (3%) or bow legs (1%) or frontal bossing (1%) with their implications for micronutrient deficiency. None of the children from the three villages were infested with the malarial parasite. On average, 54% of children from Mae Hae Tai village and 85% of children from Mae Yot village but only 4% of the children from Mae Raek village were infested with parasites. Ascaris lumbricoides was the most common infestation in all children from three villages. Conclusion: The prevalence of malnutrition was high among the Karen hill tribe children aged 1-6 years, Thailand. Most of the children suffered from upper respiratory tract infection, skin infection, scabiasis and/or diarrhrea. Nearly all of them had scaly and dry skin over their chest walls and legs which indicated essential fatty acid deficiencies. However, only 10% of them had vitamin deficiencies such as B2, C, and D.